Optimization for the degradation of food waste by a novel anti-acidification and salt-tolerant microbial consortium. Issue 1 (June 2021) - Meng, Qingbo; Gao, Yude; Li, Shuangke; Jiang, Bini; He, Mingfei; Bu, Hao; Wang, Hongling; Wu, Di
Abstract: Improving the microbial degradation capacity of food waste (FW) is a great challenge due to its acidity and high salinity. In this paper, an anti-acidification and salt-tolerant microbial consortium (AASTMC) obtained from acid and salinity mutagenesis of Bacillus amyloliquefaciens, Bacillus cereus, Yarrowia lipolytica, and Trichoderma reesei was used to degrade residential food waste. The process parameters that influenced the degradation rate of organic matter were identified by response surface methodology (RSM) with a central composite design (CCD). The effect of inoculation amount, temperature, and bulk density on the degradation rate of organic matter decreased in turn. The degradation rate of organic matter reached 94.87% under the optimum parameters of inoculation amount: 5%, bulk density: 0.04 g/cm 3, and temperature: 32.33°C.